Tuberculosis: The Interrelationship with Oral Health (Indian Journal of Forensic Medicine & Toxicology, 2020)
One-fourth of the population globally is infected utilizing a bacterial infection-tuberculosis (TB). TB remainsthe most contagious killer disease globally having 10 million people falling ill with TB. The transmissionroute of TB is through the air and when symptoms occur, Therefore, as a dentist we need to be aware oforal tuberculosis such that proper protocol can be followed in our daily practice. This article highlights theimportant oral manifestation of tuberculosis and its confirmed diagnostic criteria so that a dentist can followall the guidelines for proper management of a tuberculosis-infected dental patient.
Keywords: Dental protocols, Oral manifestations, Tuberculosis.